Emotional Quotient (EQ) dengan Motivasi Belajar Siswa pada Mata Pelajaran Fiqih di MA Muhammadiyah Aimas - Purwanti, Purwanti; Hamzah, Hamzah (Al-Fikr: Jurnal Pendidikan Islam, 2017)
This study entitled "The Relationship of Emotional Quotient with Student Learning Motivation in the Subjects of Fiqh in MA Muhammadiyah Aimas Sorong Regency" which discusses emotional quotient (emotional intelligence) can affect student motivation in fiqh subjects. The formulation of the problem in this study is whether there is a significant relationship between emotional intelligence with student motivation in the subject of Fiqh in MA Muhammadiyah Aimas, Sorong Regency? The purpose of this study is to describe the relationship of emotional intelligence with student learning motivation on fiqh subjects at MA Muhammadiyah Aimas, Sorong Regency. This type of research is quantitative using survey methods and correlational techniques. The sample of this study was the XI grade students of MA Muhammadiyah Aimas with a total of 22 students. In order to obtain the required data, the authors use the Likert scale questionnaire method. The data that has been collected is then processed using the help of the SPSS application for Windows 20.Based on the results of statistical analysis using the help of the SPSS application program for Windows 20, the results of the study showed that emotional intelligence influenced students' learning motivation in fiqh subjects in class XI students.